Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw dan Group Investigation(GI) Terhadap Hasil Belajar PPKn Siswa Kelas V Sekolah Dasar - Anastasya Septariani; Agustina Tyas Hardini (Peneliti.net, 2023)
This study aims to examine the effectiveness of the Jigsaw and Group Investigation type cooperative learning models on the learning outcomes of Civics Theme 9 of grade V elementary school students. Sampling using purposive sample technique with a total of 24 control group students and 24 experimental group students. To determine the difference in the effectiveness of the model, the T test is used in the normality and homogeneity test of the control class and the experimental class is declared normal and equal so that it can be continued for the t test. Based on the results of the t test analysis using the t-test for equality of means with Dig.2-tailed control group and group of 0.019. Because the 2-tailed significance value of both classes is more <0.05, it can be concluded that H0 is rejected and Ha is accepted, which means that the affective domain in using the Group Investigation Type Cooperative learning model and the Jigsaw Type Cooperative learning model is significant in improving learning outcomes while the results of the t-test analysis or the difference test using the t-test for equality of means with Dig.2-tailed experimental group 1 and group 2 amounted to 0.025. Because the 2-tailed significance value of both classes is more <0.05, it can be concluded that H0 is rejected and Ha is accepted, which means that the Group Investigation Type Cooperative learning model and the Jigsaw Type Cooperative learning model are significant in improving learning outcomes. This proves that the jigsaw and Group Inestigation learning models are effective in improving learning outcomes.